Seasonal Variation in Family Homeless Shelter Usage. Issue 1 (2nd January 2017) - Colburn, Gregg
Abstract: Seasonal surges in family homeless shelter usage occur in numerous communities around the United States. These surges are significant because they may place demands on shelter systems, require families to use lower quality shelter facilities, or impose significant costs on the municipalities that provide shelter services. This study uses empirical data from Hennepin County, Minnesota, to provide explanations for the seasonality of family homeless shelter usage. The results suggest that multiple factors may contribute to the surge, but that families with school-age children are the primary driver of seasonal increases in the family shelter population. This study provides initial findings that may help to improve the targeting of homelessness prevention resources.